Maximizing solar photovoltaic system efficiency by multivariate linear regression based maximum power point tracking using machine learning - Paquianadin, V.; Navin Sam, K.; Koperundevi, G. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Introduction. In recent times, there has been a growing popularity of photovoltaic (PV) systems, primarily due to their numerous advantages in the field of renewable energy. One crucial and challenging task in PV systems is tracking the maximum power point (MPP), which is essential for enhancing their efficiency. Aim. PV systems face two main challenges. Firstly, they exhibit low efficiency in generating electric power, particularly in situations of low irradiation. Secondly, there is a strong connection between the power output of solar arrays and the constantly changing weather conditions. This interdependence can lead to load mismatch, where the maximum power is not effectively extracted and delivered to the load. This problem is commonly referred to as the maximum power point tracking (MPPT) problem various control methods for MPPT have been suggested to optimize the peak power output and overall generation efficiency of PV systems. Methodology. This article presents a novel approach to maximize the efficiency of solar PV systems by tracking the MPP and dynamic response of the system is investigated. Originality. The technique involves a multivariate linear regression (MLR) machine learning algorithm to predict the MPP for any value of irradiance level and temperature, based on data collected from the solar PV generator specifications. This information is then used to calculate the duty ratio for the boost converter. Results. MATLAB/Simulink simulations and experimental results demonstrate that this approach consistently achieves a mean efficiency of over 96 % in the steady-state operation of the PV system, even under variable irradiance level and temperature. Practical value. The improved efficiency of 96 % of the proposed MLR based MPP in the steady-state operation extracting maximum from PV system, adds more value. The same is evidently proved by the hardware results. References 24, table 4, figures 14.

Вступ. Останнім часом зростає популярність фотоелектричних (ФЕ) систем, насамперед через їх численні переваги в галузі відновлюваної енергетики. Однією з найважливіших і складних завдань у ФЕ системах є відстеження точки максимальної потужності (MPP), яка необхідна для підвищення їх ефективності. Мета. ФЕ системи стикаються із двома основними проблемами. По-перше, вони демонструють низьку ефективність вироблення електроенергії, особливо в умовах низького випромінювання. По-друге, існує сильний зв’язок між вихідною потужністю сонячних батарей і погодними умовами, що постійно змінюються. Ця взаємозалежність може призвести до невідповідності навантаження, коли максимальна потужність не ефективно відбиратиметься і передаватиметься в навантаження. Цю проблему зазвичай називають проблемою відстеження точки максимальної потужності (MPPT). Для оптимізації пікової вихідної потужності та загальної ефективності генерації ФЕ систем було запропоновано різні методи керування MPPT. Методологія. У цій статті представлено новий підхід до максимізації ефективності сонячних ФЕ систем шляхом відстеження MPP та дослідження динамічної реакції системи. Оригінальність. Цей метод включає алгоритм машинного навчання багатовимірної лінійної регресії (MLR) для прогнозування MPP для будь-якого рівня освітленості і температури на основі даних, зібраних зі специфікацій сонячних ФЕ генераторів. Ця інформація потім використовується для розрахунку коефіцієнта заповнення перетворювача, що підвищує. Результати. Моделювання MATLAB/Simulink та експериментальні результати показують, що цей підхід послідовно забезпечує середню ефективність понад 96 % в режимі роботи ФЕ системи, що встановився, навіть при змінних рівнях освітленості і температурі. Практична цінність. Підвищена ефективність 96 % пропонованого MPP на основі MLR в режимі роботи, що вистачає максимум з ФЕ системи, підвищує цінність. Те саме, очевидно, підтверджують і апаратні результати. Бібл. 24, табл. 4, рис. 14.
Keywords: machine learning; maximum power point trackers; solar photovoltaic systems; машинне навчання; відстежувачі максимальної потужності; сонячні фотоелектричні системи